Pengembangan Lembar Kerja Peserta Didik sebagai Suplemen Bahan Ajar Matematika pada Materi Skala kelas V SDN 03 Pontianak Selatan - Albina Albina; Suparjan Suparjan; Rio Pranata; Hery Kresnadi; Asmayani Salimi (AS-SABIQUN, 2023)
This study aims to produce worksheet products for students as a supplement to mathematics teaching materials on a feasible scale for class V SDN 03 Pontianak Selatan. The research method used is research and development (RnD) by adapting the 4-D development model (Define, Design, Development, and Dissemination). The data sources for this research were the results of the validation of two material expert validators and display experts, the results of the student practicality questionnaire, as well as the results of student worksheet trials. The data collection technique for this research is a validator validation questionnaire, a practicality questionnaire. The results showed that during the process of developing LKPD as a supplement to mathematics teaching materials on the material on the fifth grade scale of SDN 03 Pontianak Selatan, it was carried out in 4 stages, namely the Define, Design, Development and Dissemination stages. The validity of the average percentage of LKPD from the learning aspect (material) is 4.8 with very valid criteria, and from the display aspect it is 4.8 with very valid criteria. The practicality of using LKPD by students in the first trial was 94.8% with very practical criteria and the second trial obtained an average percentage of 91.4 with very practical criteria.